Β-Ν-Methylamino-L-alanine interferes with nitrogen assimilation in the cyanobacterium, non-BMAA producer, Synechococcus sp. TAU-MAC 0499. (15th October 2020) - Vergou, Yolanda; Touraki, Maria; Paraskevopoulou, Aikaterina; Triantis, Theodoros M.; Hiskia, Anastasia; Gkelis, Spyros
Abstract: The production of β-Ν-methylamino-L-alanine (BMAA) in cyanobacteria is triggered by nitrogen-starvation conditions and its biological role, albeit unknown, is associated with nitrogen assimilation. In the present study, the effect of BMAA (773 μg L −1 ) on nitrogen metabolism and physiology of the non-diazotrophic cyanobacterium and non-BMAA producer, Synechococcus sp. TAU-MAC 0499, was investigated. In order to study the combined effect of nitrogen availability and BMAA, nitrogen-starvation conditions were induced by transferring cells in nitrogen-free medium and subsequently exposing the cultures to BMAA. After short-term treatment (180 min) and in the presence of nitrogen, BMAA inhibited glutamine synthetase, which resulted in low concentration of glutamine. In the absence of nitrogen, although there was no effect on glutamine synthetase, a possible perturbation in nitrogen assimilation is reflected on the significant decrease in glutamate levels. During the long-term exposure (24–96 h), growth, photosynthetic pigments and total protein were not affected by BMAA exposure, except for an increase in protein and phycocyanin levels at 48 h in nitrogen replete conditions. Results suggest that BMAA interferes with nitrogen assimilation, in a different way, depending on the presence or absence of combined nitrogen, providing novel data on the potential biological role of BMAA. Highlights: β-Ν-methylamino-L-alanine effect οn the cyanobacterium Synechococcus was investigated. Short-term (180 min)/long-term exposure (24–96 h) with or without nitrogen. β-Ν-methylamino-L-alanine affects the nitrogen assimilation pathway in Synechococcus . The effect depends on nitrogen availability or scarcity in the culture medium.